Impact of Sampling Frequency Offset on PRIME 1.4 PLC Systems Performance - Cortés-Arrabal, José Antonio; Sanz, Alfredo; Díez-del-Río, Luis; Cañete-Corripio, Francisco Javier (My University, 2017)
In this paper, the impact of an uncorrected sampling frequency offset (SFO) on the frame error rate (FER) of a PRIME 1.4 system is studied. It is also discussed the need of new algorithms to estimate and correct that SFO or to adopt more simpler strategies that mitigate somehow this problem, like applying in the receiver a shift to the fast-Fourier transform window towards the cyclic prefix part of the symbol.
Keywords: Cables de telecomunicaciones; PRIME; PLC; communication system; signal processing